Enhancing The Usage Of Microlearning System In Public Sector - Dirza Williansyah; Elok Savitri Pusparini (Green Publisher Indonesia, 2024)
This study explores the factors influencing the use of microlearning in the public sector by applying the DeLone and McLean Information Systems Success Model (DMISM). The study focuses on the role of overall quality, compatibility, and transformational leadership in shaping the actual use of microlearning systems. Using a quantitative approach, data were collected from 317 employees of Indonesian Government Financial Institutions (Lembaga Keuangan Pemerintah) through an online survey. The data were analyzed using covariance-based structural equation modeling (CB-SEM) in LISREL 8.8. The results indicate that overall quality, compatibility, and transformational leadership have significant and positive impacts on the actual use of microlearning systems. Among these factors, compatibility emerged as the strongest predictor of use. The findings suggest that improving the quality of microlearning content, aligning it with employee preferences, and developing a supportive leadership environment are key to increasing the adoption and effectiveness of microlearning in public sector organizations. Further research is recommended to explore other potential factors and expand the scope to other government sectors